Electric and Magnetic Fields for the Proposed Microstrip Antenna with DGS for Breast Cancer Detection - Dyg Norkhairunnisa, Abang Zaidel; Dayang Azra, Awang Mat; Lee, Y. H.; Truna, M. N.; Kho, Lee Chin; Annie, Joseph; Kuryati, Kipli (2020)
This paper presents the design of microstrip antenna with defected ground structure (DGS) for the detection of breast tumor in microwave imaging system at operating frequency of 2.45GHz. Four types of microstrip patch antennas have been designed using microstrip feed inset with grounding patches at 2.45 GHz operating frequency using dielectric substrates, FR4 (ɛr = 4.4 F / m). The results are collected via the intensity of electric (E), magnetic fields (H) and current densities. The antenna is examined with a 3D breast model structure with specific dielectric value and conductivity. From the results, it shows that antenna with design structure, Design 4 produce a good intensities values of both E and H fields respectively with the presence of the tumour, and gives the value of 7083 V/m and 35.5 A/m while without the presence of tumour is 7186 V/m and 35.8 A/m compare to other proposed antennas.